2014
DOI: 10.4187/respcare.03082
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Exercise Capacity With Lung Volumes Before and After 6-Minute Walk Test in Subjects With COPD

Abstract: INTRODUCTION:There is growing evidence that exercise-induced variation in lung volumes is an important source of ventilatory limitation and is linked to exercise intolerance in COPD. The aim of this study was to compare the correlations of walk distance and lung volumes measured before and after a 6-min walk test (6MWT) in subjects with COPD. METHODS: Forty-five subjects with stable COPD (mean pre-bronchodilator FEV 1 : 47 ؎ 18% predicted) underwent a 6MWT. Body plethysmography was performed immediately pre-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
6
0
1
Order By: Relevance
“…While the relationship between hyperinflation and exercise endurance is subject to considerable debate, 1 , 17 the lack of evidence to suggest a correlation observed here supports the theory that static hyperinflation, while important in predicting patient outcomes in COPD, is not as important as dynamic hyperinflation in predicting improvement in exercise capacity. 17 , 34 , 35 The lack of dynamic hyperinflation data is a limitation of this study; these data are technically challenging to obtain using the ESWT, due to the difficulty of performing spirometry measurements during exercise. However, measurement of lung volume during exercise should be prioritized in future studies.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…While the relationship between hyperinflation and exercise endurance is subject to considerable debate, 1 , 17 the lack of evidence to suggest a correlation observed here supports the theory that static hyperinflation, while important in predicting patient outcomes in COPD, is not as important as dynamic hyperinflation in predicting improvement in exercise capacity. 17 , 34 , 35 The lack of dynamic hyperinflation data is a limitation of this study; these data are technically challenging to obtain using the ESWT, due to the difficulty of performing spirometry measurements during exercise. However, measurement of lung volume during exercise should be prioritized in future studies.…”
Section: Discussionsupporting
confidence: 67%
“… 14 16 It has been established that exercise intolerance in COPD is related to lung hyperinflation; however, the precise relationship is complicated, partly due to debate over the relative contributions of dynamic and static hyperinflation. 1 , 8 , 17 Other factors may also play a role: exercise limitation reflects a complex interaction of ventilatory, cardiovascular, metabolic, muscular, and psychological factors, with variable relative contributions between individuals. 8 , 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Previous studies in chronic obstructive pulmonary disease have reported that hyperinflation of the lung is related to exercise tolerance; however, the precise contribution made by static or dynamic hyperinflation is still unclear. 12,27,28 The relationship between static and dynamic hyperinflation and their relative contributions to exercise tolerance have, as of yet, not been investigated in cystic fibrosis. The present study showed a significant moderate correlation between static hyperinflation (RV/TLC) and dynamic hyperinflation.…”
Section: Stevens | 1953 4 | Discussionmentioning
confidence: 99%
“…Why the marked and sustained improvements in lung hyperinflation did not translate into improvements in EET is unclear, but may be due to the complex and multifactorial processes involved in walking. It has previously been reported that static hyperinflation is less useful than dynamic hyperinflation in predicting improvements in exercise tolerance [ 20 , 22 , 23 ]. In this study, the large ICC at each study site indicated a high degree of similarity in EET measurements between the run-in period and randomisation visits.…”
Section: Discussionmentioning
confidence: 99%